(untitled) (Economics and region, 2025)
The article examines the contemporary issues of global trade conflicts. In particular, special emphasis is placed on the prerequisites, nature, and consequences of the tariff escalation initiated by the US government. The objective reasons for its introduction are indicated. On the one hand, the economic motivation of the new system of import duties is indicated, on the other hand, the current specifics of the phase of the trade conflict between China and the USA are emphasized. It is shown that, even if the introduction of new customs tariffs is suspended, negative consequences are almost inevitable for both the United States and other countries of the world. It is proven that, due to the unpreparedness of the US economic complex for full-fledged import substitution, a significant commodity deficit, inflationary pressure, and an increase in the burden of domestic debt are real. For other countries that are directly dependent on exports, the loss of the American market could be the impetus for collapses and negative political and economic transformations. It was determined that China, despite significant losses from the tariff escalation initiated by the United States, approached it more prepared and may reorient its own exports to European markets. The conclusion is made that trade conflicts, despite the short-term benefits for the initiating country, in conditions of incomplete globalization of commodity markets, will have long-term negative consequences associated with loss of confidence, low credit ratings, significant inflationary expectations, weak economic conditions, and reduced domestic demand. In addition, as the study shows, the overall cumulative effect on the global economy will be quite stressful, causing a drop in commodity prices, significant fluctuations in stock markets, changes in logistics trajectories, and possible supply disruptions.Thus, it is shown that the current state of global trade openness is under threat and coincides with the interwar period of 1919-1939. This gives every reason to identify it as a stage of neo-autarkic protectionism with the collapse of stable ties and regional trade groupings in favor of isolationism and comprehensive import substitution.